2021
DOI: 10.3390/molecules26082105
|View full text |Cite
|
Sign up to set email alerts
|

Protein O-Fucosyltransferase 1 Undergoes Interdomain Flexibility in Solution

Abstract: Protein O-fucosyltransferase 1 (PoFUT1) is a GT-B fold enzyme that fucosylates proteins containing EGF-like repeats. GT-B glycosyltransferases have shown a remarkable grade of plasticity adopting closed and open conformations as a way of tuning their catalytic cycle, a feature that has not been observed for PoFUT1. Here, we analyzed Caenorhabditis elegans PoFUT1 (CePoFUT1) conformational behavior in solution by atomic force microscopy (AFM) and single-molecule fluorescence resonance energy transfer (SMF-FRET).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Despite the great power of enzymatic processes, their potential has not been fully exploited, mainly due to the limited understanding of the mechanisms regarding the assembly and dissociation between reacting molecules. Recent advances in imaging methods have demonstrated that it is possible to make direct observations of the dynamic behavior of single molecules [3,4] and to determine the mechanisms of action at the single-molecule level [5][6][7]. Among the available singlemolecule methods, those designed to measure forces between molecules or within an individual molecule stand out [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great power of enzymatic processes, their potential has not been fully exploited, mainly due to the limited understanding of the mechanisms regarding the assembly and dissociation between reacting molecules. Recent advances in imaging methods have demonstrated that it is possible to make direct observations of the dynamic behavior of single molecules [3,4] and to determine the mechanisms of action at the single-molecule level [5][6][7]. Among the available singlemolecule methods, those designed to measure forces between molecules or within an individual molecule stand out [8].…”
Section: Introductionmentioning
confidence: 99%
“…GTs have been well-characterized via both molecular dynamics simulations and static crystal structures. ,, However, experiments designed to report on in-solution dynamics, such as 19 F NMR spectroscopy for PimA, single-molecule Förster resonance energy transfer for Fut1, and intrinsic tryptophan fluorescence for HepI, , are less common. This gap in characterization may explain the difficulties faced in identifying potent inhibitors for this class of enzymes.…”
mentioning
confidence: 99%
“…On the contrary, 2D images for GvFFTR and CaFFTR2 homodimers, despite displaying some particularly preferred topologies, exhibit a range of them, with some features appearing more elongated and others slightly more compact ( Figure 2 a,b; see 2D images for homodimers). Considering that (i) the protein-mica interactions are weaker than covalent or other protein:ligand interactions, (ii) AFM imaging enables transient dynamical conformations to occur without losing protein functionality, structure and quaternary conformations [ 21 , 25 ], and (iii) conformations visualized agree with other parallel single molecule studies as small angle X-ray scattering (SAXS) experiments [ 26 ] and single-molecule fluorescence resonance energy transfer (SMF-FRET) measurements [ 27 ], the AFM images here presented must reflect homodimers with a slightly different relative disposition of their disulfide domains relative to the main protein core ( Figure 5 ). Nonetheless, all GvFFTR and GaFFTR2 images clearly reflect FR conformations, in agreement with the evaluated oxidized states.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mica surface chemistry hardly alters the morphology, conformation, or association of the molecules, and in general, only causes the molecules, or their complexes, to be weakly immobilized by some area of their surface, preferably mainly by electrostatic adsorption through their exposed hydroxyl groups [ 28 , 29 ]. Therefore, imaging of enzymes by AFM at nearly physiologically relevant conditions, in the presence of reactants, products, or partners, is nowadays even used to understand catalytic pathways that occur through the formation of specific transient quaternary organizations [ 21 , 30 ], or even through large conformational changes upon ligand binding [ 26 , 27 ]. Nonetheless, there have been few studies evaluating protein morphology changes in detail [ 20 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%